Functional characterization of PhoPR two component system and its implication in regulating phosphate homeostasis in Bacillus anthracis - Aggarwal, Somya; Somani, Vikas Kumar; Gupta, Vatika; Kaur, Jaspreet; Singh, Damini; Grover, Abhinav; Bhatnagar, Rakesh (Biochimica et biophysica acta. General subjects, 2017)
Recent report on importance of phosphate starvation (PS) in Bacillus anthracis (BA) pathogenesis warrants further investigation of the underlying regulatory mechanism. Potential role of PhoPR two component system (TCS) in phosphate homeostasis and virulence of several pathogens necessitates the study of annotated PhoPR in BA. Expression of phoP and phoR was analyzed using qRT-PCR. PhoPR was characterized biochemically. DNA-protein interaction was analyzed by EMSA. Docking was done to predict PhoPR interacting residues with further validation by mutational studies. pHCMC05 was used to overexpress PhoP in BA. In silico analysis revealed Bas4483-4484, as putative PhoR–PhoP. Their expression was decreased with increasing phosphate concentration reflecting some role in PS. Both PhoP (response regulator) and PhoR (histidine kinase) showed characteristic property of TCS i.e., autophosphorylation and phosphotransfer. PhoR showed both kinase and phosphatase activity. PhoP bound with promoter of PS marker genes. In silico and in vitro analysis revealed role of PhoRH370 and PhoPD10, PhoPD53, PhoPM55 in PhoPR interaction. Challenge studies showed decreased survival of mice infected with BApHCMC05-PhoP. This study affirms that PhoPR forms functional TCS which is upregulated under PS. PhoP binding with promoter of PS marker genes indicates its possible role in regulating PS response. Low survival of mice infected with BApHCMC05-PhoP suggests its role in BA virulence. Considering the significance of PS in BA infection, possible role of PhoPR in its regulation and exclusive presence of TCS in prokaryotes, PhoP can be proposed as potential drug target against anthrax. [Display omitted] •Phosphate starvation (PS) promotes pathogenesis of B. anthracis (BA) within host.•PhoP and PhoR of BA form a functional two component system, regulating PS response.•PhoP is implicated in regulation of PS marker genes.•H370 of PhoR and D10, D53 and M55 of PhoP are involved in PhoPR interaction.•Exclusive in microbes, homology in pathogens, role in virulence & PS make PhoP as a good drug target.